Evaluation of Preexposure (PrEP) Eligibility Criteria, Using Sexually Transmissible Infections as Markers of Human Immunodeficiency Virus (HIV) Risk at Enrollment in PrEPX, a Large Australian HIV PrEP Trial. (7th May 2018) - Cornelisse, Vincent J; Fairley, Christopher K; Stoove, Mark; Asselin, Jason; Chow, Eric P F; Price, Brian; Roth, Norman J; Willcox, Jeff; Tee, B K; Penn, Matthew; Chang, Christina C; Armishaw, Judith; et al.
Abstract: Background: To determine participants' human immunodeficiency virus (HIV) risk, the Australian preexposure prophylaxis (PreEPX) trial used 6 eligibility criteria derived from the US Centers for Disease Control and Prevention PrEP guidelines. Participants who fulfilled no eligibility criteria could be enrolled if clinically assessed to need PrEP. This study evaluated whether PREPX eligibility criteria correlated with biological HIV risk markers—namely, syphilis, anorectal chlamydia, or anorectal gonorrhea (sexually transmitted infections [STIs]). Methods: We calculated adjusted odds ratios (aORs) to assess whether eligibility criteria predicted STI diagnoses at enrollment. Results: We included 1774 participants, of whom 10.2% tested positive for STIs. Eligibility criteria predicted STI diagnoses as follows: (1) aOR 2.5 (95% confidence interval [CI], 1.4–4.4) for condomless anal intercourse (CLAI) with an HIV-positive regular sexual partner (RSP) with detectable viral load; (2) aOR 1.8 (95% CI, 1.3–2.5) for receptive CLAI with casual sexual partners; (3) aOR 1.8 (95% CI, 1.3–2.5) for previous STIs; (4) aOR 2.1 (95% CI, 1.4–3.0) for methamphetamine use; (5) aOR 0.8 (95% CI, .6–1.1) for unsuccessful condom use; and (6) aOR 1.0 (95% CI, .7–1.4) for insertive CLAI when uncircumcised. Of participants enrolled outside eligibility criteria, 7.1% had STIs. Conclusions: Eligibility criteria 1–4 predicted diagnoses of STIs, but eligibility criteria 5 and 6 did not. Our findings support the use of PrEP eligibility criteria recommended in current guidelines. Participants enrolled outside the eligibility criteria had substantial prevalence of STIs, suggesting that people who request PrEP but do not fulfill eligibility criteria may nonetheless need PrEP. Abstract : The PrEPX trial used eligibility criteria based on the US Centers for Disease Control and Prevention PrEP guidelines. We evaluated whether these eligibility criteria correlated with biological human immunodeficiency virus (HIV) risk markers—namely, syphilis, anorectal chlamydia, and anorectal gonorrhea.